Communicating Philanthropy: Multiple Representations to Multiple Stakeholders? - Moir, Lance (Cranfield University, 2003)
Why do firms engage in Corporate Philanthropy? What role does communication play in the giving activity? This paper examines the accounts given by 100 large firms in the UK for their involvement with the Arts. Formal content analysis is undertaken of annual reports, social accounts, websites and press releases. It finds that firms speak most of wanting to be a good corporate citizen and attend to communities. There is little overt marketing in contrast to other studies that find that corporate philanthropy can be aligned to advertising. This research finds support for strategic philanthropy, but that the strategic intent may be more about meeting a form of social contract or securing a licence to operate. This would support the stakeholder and political models of giving rather than neo-classical and altruistic models. This paper adds to the literature by combining the corporate philanthropy and social accounting literatures. The ability to communicate may be an important part of the motivation for corporate giving. Paper presented at the 2003 Academy of Management Conference